2014
DOI: 10.1002/2013wr014834
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic model of streamflow for urbanized basins

Abstract: Given the critical role of the streamflow regime for instream, riparian, and floodplain ecosystem sustainability, modeling the long-term effect of urbanization on streamflow is important to predict possible changes in stream ecosystems. Since flow duration curves are largely used to characterize the streamflow regime and define indices for stream ecosystem health, we present two stochastic models, with different levels of complexity, that link the key physical features of urbanized basins with rainfall variabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 83 publications
2
26
0
3
Order By: Relevance
“…Recently, the model has been extensively applied to characterize river flow regimes and a variety of biotic and anthropogenic riverine processes (see e.g. [7,8,16,19,26,28,29,33,34]). The ability of the model to reproduce observed probability distributions in the range of low to medium streamflows has been the object of previous studies [4,15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the model has been extensively applied to characterize river flow regimes and a variety of biotic and anthropogenic riverine processes (see e.g. [7,8,16,19,26,28,29,33,34]). The ability of the model to reproduce observed probability distributions in the range of low to medium streamflows has been the object of previous studies [4,15].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the focus of the IND on online (i.e., real time) applications, computationally efficient routines for parameter inference are important. For time series data, the likelihood function is given as a product of one-step-ahead conditional densities [Box et al, 2008;Madsen, 2008]. This approach is more efficient and easier to implement than sampling from the multivariate likelihood function when accounting for all the…”
Section: Parameter Estimation In the Ind Approachmentioning
confidence: 99%
“…Runoff modeling in urban hydrology distinguishes itself from its counterpart in natural catchment hydrology by the usually smaller temporal and spatial scales involved in peak discharge generation. Typical time steps for peak discharge simulations are 6 [Kleidorfer et al, 2009] to 15 min [Breinholt et al, 2012], but seconds [Freni et al, 2009] to days [Mej ıa et al, 2014] have been reported. Typical study areas of sewer watersheds range from dozens [Del Giudice et al, 2015] to more than 1000 ha [Breinholt et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the larger flows discharged in urban streams increase the export of nutrients and pollutants, and cause a decrease in biodiversity with associated detrimental effects to the health of riparian ecosystems (Walsh et al, 2005b). Although traditionally focused on peak flows, the management of urban stormwater runoff is now often directed toward restoration of the overall streamflow regime, which includes the dynamic range of streamflow fluctuations (see Mejía et al, 2014). Therefore, the management of urban streams 35 has been increasingly focused on controlling urban stormwater runoff with the intent to limit the streamflow during floods while also maintaining adequate flow rates during dry periods (Debusk et al, 2011;Burns et al, Hydrol.…”
Section: Introductionmentioning
confidence: 99%